การพัฒนาโปรแกรมการศึกษานอกระบบโรงเรียนเพื่อเสริมสร้างสมรรถนะการสื่อสารระหว่างบุคคลสำหรับนิสิตนักศึกษา - เรข์ณพัศ ภาสกรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
The purposes of this research were to 1) analyze interpersonal communication competencies for undergraduate students; 2) develop a non-formal education program to enhance interpersonal communication competencies for undergraduate students; 3) present the application guidelines of a non-formal education program. There are 3 groups of samples; 1) 1,101 undergraduate students who were selected by using multi-stage stratified random sampling; 2) 30 undergraduate students participating in the activities; 3) 20 experts and student representatives for focus group discussion. The statistics employed for analysis were frequency (), percentage (%), standard deviation (S.D.), t-test, p-value and content analysis. The findings can be summarized as follows 1. The mean scores of interpersonal communication competencies for undergraduate students were at high level in motivation, knowledge and skill. 2. A developed non-formal education program was consisted of 8 processes: 1) identification of the basis for programming, 2) situational analysis of community and clientele, 3) identification of desired outcomes, 4) identification of resources and support, 5) design of an instructional plan, 6) program of action, 7) accountability of resources, and 8) communication of the value of the program; and 12 components: 1) rational criterion, 2) objectives, 3) content, 4) learners qualification, 5) facilitators qualification, 6) learning method, 7) learning process, 8) learning technique, 9) resources and materials, 10) learning evaluation, 11) learning environment, and 12) learning outcomes. The results showed that the samples have motivation, knowledge and skills significantly higher than the one before the experiment by 0.05 point. 3. The application guidelines of a developed non-formal education program were consisted of three components: facilitator qualifications, program management, and creating involvement of stakeholders. Factors affecting the success of program application include learners, teams, and cultural context.